Construction and Comprehension of Fictional Dystopia: A Cognitive Study of Anna Burns's Milkman - Farsi, Roghayeh (Archīum Ateneo, 2024)
This paper investigates how fictional dystopia is constructed and comprehended, relying upon the cognitive operations of categorization and positioning. It argues that characters develop out of tensions between self-aligned categories and others-aligned ones. The argument is carried out through a detailed analysis of Burns’s fictional dystopia, Milkman (2018). It divides the novel along three story levels, each level examining how the narrator, as the presenting self, positions her presented self with respect to other characters, to herself, and to readers. The study also looks for the narrator’s cognitive urges for portraying herself along the imposed categories and inflicted positions. It concludes that there is an intertwined relationship between categorization and positioning, taking categories as manifestation of one’s position.